2018
DOI: 10.1016/j.jhep.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 exacerbates liver sterile inflammation by amplifying neutrophil extracellular trap formation

Abstract: Liver ischemia and reperfusion injury results in the formation of neutrophil extracellular traps, which contribute to organ damage in liver surgeries. Herein, we show that IL-33 is released from liver sinusoidal endothelial cells to promote NET formation during liver I/R, which exacerbates inflammatory cascades and sterile inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 42 publications
(63 reference statements)
6
90
1
Order By: Relevance
“…These findings argue against acute formation of NETs after reperfusion. A previous study has suggested evidence for NET formation induced by ischemia/reperfusion injury in humans, (3) but this study only demonstrated elevated MPO-DNA complex levels in samples taken on postoperative day 1 without directly linking these elevated levels to ischemia/reperfusion injury.…”
Section: To the Editorcontrasting
confidence: 78%
“…These findings argue against acute formation of NETs after reperfusion. A previous study has suggested evidence for NET formation induced by ischemia/reperfusion injury in humans, (3) but this study only demonstrated elevated MPO-DNA complex levels in samples taken on postoperative day 1 without directly linking these elevated levels to ischemia/reperfusion injury.…”
Section: To the Editorcontrasting
confidence: 78%
“…In addition, ST2 blockade completely ameliorated neutrophilia in IFNγ −/− Prf1 −/− mice (Figure H). We hypothesize that this is due to reduced CD8+ T cell activation, which we know is needed for neutrophilia; yet it is also known that IL‐33 signaling can act directly on neutrophils to exacerbate inflammation . Overall, these data show that IFNγ is not necessary for development of a CD8‐driven HLH‐like disease in a novel murine model.…”
Section: Resultsmentioning
confidence: 79%
“…Hepatic ischemia-reperfusion (I/R) injury is a complication of hepatic surgery, and it can arise after liver resection and transplantation [1,2]. Hepatic I/R injury induces oxidative stress, inflammation, and other disorders in the liver, thus leading to the liver damage in patients requiring liver surgery [3][4][5][6]. However, the mechanisms underlying the I/R injury are not completely understood.…”
Section: Introductionmentioning
confidence: 99%